Faktor-faktor yang Berhubungan dengan Kejadian Gigitan Hewan Penular Rabies di Kelurahan Nonohonis Kota Soe Kabupaten TTS Tahun 2023 - Bernadethe Constantia Piana Sogen (Yayasan Literasi Sains Indonesia, 2024)
Extraordinary Events (EE) occur in infectious diseases, where rabies is a disease transmitted through the bite of Rabies Transmitting Animals (RTA). Rabies bite cases were spread throughout the Soe City Health Center working area with the highest case in Nonohonis Subdistrict with 68 cases in 2023. The objective of this study was to analyze the relationship between knowledge, age, RTA husbandry practices, contact with RTA, RTA health examination, RTA vaccination with the incidence of Rabies Transmition Animal Bites (RTAB) in Nonohonis Village, Soe City, TTS Regency. This type of research uses an analytical survey method, with a case control design. The population was all people living in Nonohonis Village, Soe City, TTS Regency, which was divided into two groups, namely cases and controls totaling 68 and 4,202 respectively. The number of samples was 61 divided into two groups, namely cases and controls with a ratio of 1: 1 so that the total sample was 122 people. The case sampling technique used simple random sampling and the control sample was taken after matching. Data analysis used univariate and bivariate analysis. The results of bivariate analysis using chi-square test showed a significant association between knowledge (p-value=0.000), age (p-value=0.000), RTA husbandry practices (p-value=0.000), contact with RTA (p-value=0.046), RTA health examination (p-value=0.001), RTA vaccination (p-value=0.000) with the incidence of rabies- transmition animal bites. Based on the results of the study, it can be concluded that knowledge, age, RTA husbandry practices, contact with RTA, RTA health examination, HPR vaccination have a significant relationship with the incidence of RTAB.